2013
DOI: 10.1186/1471-2458-13-202
|View full text |Cite
|
Sign up to set email alerts
|

Yellow fever vaccination coverage following massive emergency immunization campaigns in rural Uganda, May 2011: a community cluster survey

Abstract: BackgroundFollowing an outbreak of yellow fever in northern Uganda in December 2010, Ministry of Health conducted a massive emergency vaccination campaign in January 2011. The reported vaccination coverage in Pader District was 75.9%. Administrative coverage though timely, is affected by incorrect population estimates and over or under reporting of vaccination doses administered. This paper presents the validated yellow fever vaccination coverage following massive emergency immunization campaigns in Pader dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…the proportion of children vaccinated among those targeted, for the phase 2 measles campaign in Jharkhand was 91.6%—higher than the 61.0% coverage estimated by this survey [ 11 ]. Administrative coverage is commonly used to asses campaign coverage, but is often unreliable [ 17 , 18 ]. Because of the noted discrepancy in administrative and survey coverage, future measles campaigns could include a post-campaign coverage survey to reliably estimate vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…the proportion of children vaccinated among those targeted, for the phase 2 measles campaign in Jharkhand was 91.6%—higher than the 61.0% coverage estimated by this survey [ 11 ]. Administrative coverage is commonly used to asses campaign coverage, but is often unreliable [ 17 , 18 ]. Because of the noted discrepancy in administrative and survey coverage, future measles campaigns could include a post-campaign coverage survey to reliably estimate vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…However, five studies did not mention if the tool used was standardised 29 , 34 , 42 , 45 , 46 . Ten studies collected information from proxies (parents or guardians of vaccinated children) 29 32 , 34 , 36 , 43 – 46 . All the studies calculated vaccination coverage as the ‘number vaccinated divided by the number of the targeted population’.…”
Section: Resultsmentioning
confidence: 99%
“…SIAs: Twelve studies reported vaccination coverage for SIAs. Three studies reported coverage data on meningococcal serogroup A (PsA-TT) vaccine 29 , 30 , 44 , five on measles vaccine 31 , 32 , 34 , 56 , 57 and two on yellow fever vaccine 36 , 43 . Each of the remaining two studies reported on one vaccine; cholera 38 and meningococcal bivalent polysaccharide A/C vaccine 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Adult vaccination in Africa has mostly focused on pregnant women for whom vaccines are delivered at ante-natal clinics during routine visits. Mandatory vaccination for travellers to certain countries and mass vaccination campaigns following VPD outbreaks also serve as opportunities for adult vaccination [15][16][17]. Largely, most adults in Africa remain unvaccinated despite the vaccines being available.…”
Section: Introductionmentioning
confidence: 99%